Oncologic Diseases as a Risk Factor for Cryptogenic Stroke - G. R. Ramazanov; E. A. Kovaleva; N. A. Shamalov (Неотложная медицинская помощь)
Background. Acute cerebrovascular accidents in general, and ischemic stroke (IS) in particular, are multifactorial diseases with extremely heterogeneous and numerous risk factors. Currently, despite the development of diagnostic technologies, in approximately 25% of patients with IS, it is not possible to establish the causes and mechanism of its development (the so-called cryptogenic stroke (CS)). As a result, the optimal antithrombotic therapy as a secondary prevention in this group of patients remains unclear. It was found that in 10–20% of patients with CS, a detailed examination reveals oncological disease (OD). It is highly likely that the prevalence of OD-related IS will increase. The US National Cancer Registry has shown a decrease in mortality in patients with the most common forms of OD (lung, breast and prostate cancer). Active OD is a proven risk factor for both IS and other thrombotic events. Nevertheless, about 50% of IS in patients with OD are classified as cryptogenic, which significantly exceeds this indicator in patients without OD. This is associated with the difficulties of intravital diagnosis of the pathogenetic mechanism of IS in patients with OD.Aim of study. Raising the awareness of neurologists about the causes, pathogenetic mechanisms of development and methods of diagnosing IS in patients with OD.Materials and methods. To achieve this goal, the results of scientific research on OD as a risk factor for CS were analyzed. The literature search was carried out in electronic search engines Scopus, eLibrary, PubMed by keywords: ischemic stroke, cryptogenic stroke, cancer, pathogenesis of ischemic stroke. Scientific articles published between 1856 and 2021 were selected for analysis, 45% of the analyzed papers on the topic of CS were published not earlier than 5 years ago.Conclusion. The cause of the development of ischemic stroke can be both the oncological process itself and the means and methods of treating it. Despite the fact that in 10–20% of patients with cryptogenic stroke OD is diagnosed, the question remains whether patients with cryptogenic ischemic stroke should be screened for latent oncological pathology, and if so, how full should the screening be. Typical radiological patterns of ischemic stroke in patients with OD are multiple foci of acute cerebral ischemia in different vascular areas, which may indicate a cardioembolic nature and, in particular, non-bacterial thrombotic endocarditis. Lifetime diagnosis of the causes of cryptogenic stroke in patients with OD is extremely difficult. Since nonbacterial thrombotic endocarditis is one of the leading causes of cryptogenic stroke in the setting of cancer, it is advisable to perform transesophageal echocardiography due to the low sensitivity of transthoracic echocardiography.